Evaluation of The Allocation of Education Unit Operational Budget (BOSP) to Improve the Quality of Literacy-Based Learning - H. Soro , Suharyanto; Supriyatin, Rati; Komalasari, Dini (Global Education Journal, 2025)
Education Unit Operational Costs (BOSP) are a crucial component in education policy that plays a vital role in ensuring the continuity of quality learning. This study aims to evaluate the budget allocation of Education Unit Operational Costs (BOSP) in supporting the improvement of literacy-based learning quality at SDN Tanara, Pangalengan District, Bandung Regency. The method used in this study is a qualitative case study approach with the CIPP (Context, Input, Process, Product) evaluation model. Data were obtained through in-depth interviews with the principal, BOSP treasurer, and teacher in charge of literacy, as well as through questionnaires to teachers and students, observations of literacy activities, and documentation of school financial planning. The results of the study indicate that the policy and planning for the allocation of BOSP funds for literacy activities have been prepared in a participatory manner, with a focus on the provision of reading materials, teacher training, and strengthening reading programs. The implementation of the program has been quite effective, although there are still variations in quality between classes. A number of obstacles were found, such as limited teacher competence, minimal parental participation, and complicated fund administration procedures. To address this, schools implement various optimization strategies, such as literacy integration in learning, reading corner book rotation, and teacher capacity building. This study recommends that schools and policy makers improve the allocation and effectiveness of BOSP fund management, strengthen teacher training, and encourage active parental involvement in building a culture of literacy in the home and school environment.